1995
DOI: 10.1016/0014-5793(95)00772-2
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of voltage‐activated Na+ currents in two prostatic tumour cell lines: contribution to invasiveness in vitro

Abstract: The voltage-gated ionic currents of two rodent prostatic cancer cell lines were investigated using the whole-cell patch clamp technique. The highly metastatic Mat-Ly-Lu cells expressed a transient, inward Na ÷ current (blocked by 600 nM tetrodotoxin), which was not found in any of the weakly metastatic AT-2 cells. Although both cell lines expressed a sustained, outward K ÷ current, this occurred at a significantly higher density in the AT-2 than in the Mat-Ly-Lu cells. Incubation of the MatLy-Lu cell line with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
204
1
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(227 citation statements)
references
References 38 publications
(30 reference statements)
20
204
1
2
Order By: Relevance
“…Each cell line was then incubated in 0.8 ml normal growth medium with or without the added drug for 48 h, with an identical solution change at 24 h. Proliferation was quantified using the colorimetric 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT) assay. 4 Accordingly, sterile 0.2 ml MTT (5 mg/ml made up in the growth medium) was added to the 0.8 ml of fresh medium in the tissue culture dishes. The plates were then incubated at 371C for 6 h. The medium was then removed and replaced with 1 ml DMSO to lyse the cells.…”
Section: Proliferation and Toxicity Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Each cell line was then incubated in 0.8 ml normal growth medium with or without the added drug for 48 h, with an identical solution change at 24 h. Proliferation was quantified using the colorimetric 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT) assay. 4 Accordingly, sterile 0.2 ml MTT (5 mg/ml made up in the growth medium) was added to the 0.8 ml of fresh medium in the tissue culture dishes. The plates were then incubated at 371C for 6 h. The medium was then removed and replaced with 1 ml DMSO to lyse the cells.…”
Section: Proliferation and Toxicity Assaysmentioning
confidence: 99%
“…Furthermore, diagnosis of metastatic PCa by measurement of prostate-specific antigen is prone to significant uncertainty. 3 We showed previously that functional voltage-gated sodium channels (VGSCs) are expressed specifically in strongly metastatic cells of rat 4 and human PCa. 5 VGSC activity has also been shown to enhance several cellular behaviours linked to metastasis, including morphological change, 6 endocytosis/secretory membrane activity, 7 galvanotaxis, 8 invasion, 4,5,9 lateral motility 10 and interaction with the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Thus, VGSCs could actively contribute to the metastatic process. The VGSC a-subunit (VGSCa) expressed at the highest levels and most likely to be responsible for ion pore formation was Na v 1.7.…”
Section: Introductionmentioning
confidence: 99%
“…Details of the patch pipettes, solutions and the wholecell recording protocols have been described previously (Grimes et al 1995;Laniado et al 1997;Fraser et al 2005). Patch pipettes (tip resistances, ~5 MΩ) were filled with a solution designed to block the outward K + currents; the composition was as follows (in mM): NaCl 5, CsCl 145, MgCl 2 2, CaCl 2 1, HEPES 10 and EGTA 11, adjusted to pH 7.4 with 1 M CsOH.…”
Section: Patch Clamp Recordingmentioning
confidence: 99%
“…Several studies have shown that functional VGSC expression occurs in a variety of carcinomas and promotes metastatic behaviour. Such carcinomas include BCa as well as cancers of the prostate (Grimes et al 1995;Laniado et al 1997;Nakajima et al 2009), lung (Onganer and Djamgoz 2005;Campbell et al 2013), colon (House et al 2010) and cervix (Diaz et al 2007). It has been suggested, therefore, (1) that VGSC up-regulation is an early event in metastatic progression and (2) that VGSC expression is a 'switch,' necessary and sufficient for engaging cancer cells in a highly invasive state.…”
mentioning
confidence: 99%